Immersive virtual reality training to identify and investigate child abuse: a review of emerging progress and future directions - Reddy, Tanvi; Sinha, Shreya Mona (Frontiers in Virtual Reality, 2025)
Child abuse is a pervasive global issue with enduring consequences, and conversations with children are central to its detection and intervention. However, these conversations are fraught with psychological and developmental complexities, and professionals across legal, medical, and educational fields often report feeling ill-equipped to navigate them. Most critically, forensic interviewers frequently rely on coercive questioning techniques, undermining the validity of children’s testimonies in court. Traditional training methods to elicit reliable verbal disclosures have remained ineffective, driving interest in using immersive virtual reality (VR) to provide simulated conversations with child victims. To assess the existing evidence base, a reproducible systematic search was conducted across APA PsycInfo, PsycArticles, PubMed, Mendeley, and Google Scholar. While early studies suggest immersive VR training enhances professionals’ self-efficacy and learning outcomes, the empirical validation remains limited, indicating critical gaps for future studies to address. This scoping review synthesizes emerging research on immersive VR for child protection training, evaluating its efficacy, limitations, and methodological rigor across professional contexts.